Pharmacovigilance on cannabidiol as an antiepileptic agent - Ammendolia, Ilaria; Mannucci, Carmen; Cardia, Luigi; Calapai, Gioacchino; Gangemi, Sebastiano; Esposito, Emanuela; Calapai, Fabrizio (Frontiers in Pharmacology, 2023)
Cannabidiol (CBD) is an active chemical contained in the plant Cannabis sativa. It is a resorcinol-based compound crossing the blood-brain barrier but not causing euphoric effects. CBD exerts a plethora of pharmacological effects of therapeutic interest. CBD has been authorized in European Union as anticonvulsivant against serious infantile epileptic syndromes but its safety profile is still not sufficiently described. With the aim to expand information on safety of CBD use as anti-epileptic agent, beyond the most common side effects known through clinical studies, an analysis of serious case reports on suspected adverse reactions (SARs) to CBD licensed as antiepileptic drug found in EudraVigilance database is reported in this article. EudraVigilance is a system purchased by the European Medicines Agency (EMA) monitoring the safety of medicines of medicinal products marketed in Europe. Most frequent among serious SARs to CBD in EudraVigilance were: aggravation of epilepsy, hepatic disorders, lack of efficacy, somnolence. On the basis of our analysis, precautions to be adopted for CBD medical use as antiepileptic are: awareness of use with other drugs, appropriate surveillance of potential adverse effects, more attention towards possible aggravation of epilepsy and drug effectiveness.